2018
DOI: 10.3233/jad-180048
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting Amyloid PET Positivity in Amnestic Mild Cognitive Impairment

Abstract: Background: Most clinical trials focus on amyloid-␤ positive (A␤+) amnestic mild cognitive impairment (aMCI), but screening failures are high because only a half of patients with aMCI are positive on A␤ PET. Therefore, it becomes necessary for clinicians to predict which patients will have A␤ biomarker. Objective: We aimed to compare clinical factors, neuropsychological (NP) profiles, and apolipoprotein E (APOE) genotype between A␤+ aMCI and A␤-aMCI and to develop a clinically useful prediction model of A␤ pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…A few studies have previously proposed different types predictive models for detecting cerebral amyloid positivity based on demographics, NP tests, MRI measures, and blood or CSF-based biomarkers [33][34][35][36][37][38]. For example, Kander et al [34] reported AUCs of 0.59-0.67 for individual NP tests, AUC of 0.64 using all NP tests, and AUC of 0.64 for hippocampal volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have previously proposed different types predictive models for detecting cerebral amyloid positivity based on demographics, NP tests, MRI measures, and blood or CSF-based biomarkers [33][34][35][36][37][38]. For example, Kander et al [34] reported AUCs of 0.59-0.67 for individual NP tests, AUC of 0.64 using all NP tests, and AUC of 0.64 for hippocampal volume.…”
Section: Discussionmentioning
confidence: 99%
“…Palmqvist et al [36] applied a forward selection logistic regression model to demographics, ApoE4, NP tests, and white matter lesions for prediction of amyloid positivity and achieved AUCs of 0.80-0.82 in ADNI. Kim et al [35] used similar variables and using logistic regressions, developed a nomogram that achieved predictive AUCs of 0.74-0.77.…”
Section: Discussionmentioning
confidence: 99%
“…We defined Aβ PET positivity (PET+) for the three different types of PET images as follows: 1) Global PiB SUVR (assessed from the volume-weighted average SUVR of 28 bilateral cerebral cortical VOIs) of greater than 1.5 as described in our previous study, 20 2) visual rating score on florbetaben PET of 2 or 3 on the brain Aβ plaque load scoring system, 21 3) positive visual interpretation of 18 F-flutemetamol PET in any one of the five brain regions (frontal, parietal, posterior cingulate and precuneus, striatum, and lateral temporal lobes) in either hemisphere. 22 …”
Section: Methodsmentioning
confidence: 99%
“…However, risk factor models do not directly translate into clinically useful or practical algorithms. Many models lack external validation, include inputs with small effect sizes, or include inputs that are burdensome or costly (e.g., extensive neuropsychological testing or imaging) [10,15–17]. Recently, more practical algorithms to estimate the likelihood of Aβ positivity among patients with subjective cognitive decline (SCD) or mild cognitive impairment (MCI) were published [11,18,19].…”
Section: Introductionmentioning
confidence: 99%